1998
DOI: 10.1016/s0895-7061(98)00056-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased Erythrocyte Aggregation in Spontaneously Hypertensive Rats

Abstract: Alterations of red blood cell (RBC) aggregation and plasma viscosity are major contributors to the changes in blood rheologic properties that cause an increase in peripheral vascular resistance during the development of hypertension. Although basic research and clinical study have provided considerable understanding of the pathophysiology of hypertension, the objective of this study was to determine whether an increase in RBC aggregability and plasma viscosity precede or accompany the development of high arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 21 publications
4
71
0
1
Order By: Relevance
“…Increased blood concentration of Fg results in an increase of blood viscosity (Lominadze et al, 1998) and therefore an increase in blood flow shear stress (Chien et al, 1966). This contributes to an activation of ECs expressing and/or activating various integrins and adhesion molecules including ICAM-1 (Springer, 1990), a well-known Fg receptor (Plow et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased blood concentration of Fg results in an increase of blood viscosity (Lominadze et al, 1998) and therefore an increase in blood flow shear stress (Chien et al, 1966). This contributes to an activation of ECs expressing and/or activating various integrins and adhesion molecules including ICAM-1 (Springer, 1990), a well-known Fg receptor (Plow et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…During inflammation, overexpression of interleukin-1 and interleukin-6 leads to an increased blood content of Fg (Nakamura et al, 1996). Elevated blood level of Fg is a biomarker of inflammation and high risk factor for many cardiovascular (Danesh et al, 2005) and cerebrovascular disorders (del Zoppo et al, 2009) such as hypertension (Lominadze et al, 1998) and stroke (Eidelman and Hennekens, 2003). While normal blood concentration of Fg is about 2 mg/mL (Lominadze et al, 2010), during hypertension it reaches 4 mg/mL (Lominadze et al, 1998) and 3.6 mg/mL after ischemic stroke in humans (Eidelman and Hennekens, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[25] The washed cells were suspended in homologous plasma with a volume ratio of 1 part of erythrocytes to 200 parts of plasma. An assessment of plasma-induced RBC aggregation was done under static conditions by direct visualization of the process.…”
Section: Rbc Aggregation and Rbc Aggregability Assessmentmentioning
confidence: 99%
“…Alterations of major determinants of the blood's rheological properties observed in hypertensive disease include increased viscosity of blood [23,24] and plasma, [23][24][25] increased hematocrit [24,25] and increased levels of high molecular weight plasma proteins including fibronectin, [25] immunoglobulin-A [26] and particularly fibrinogen (Fb), [3] which are the major determinants of plasma viscosity. Furthermore, it has been shown that RBC aggregation, which has the most significant effect on blood rheological properties, is increased during hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation